2014
DOI: 10.1016/j.jphotobiol.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Continuing to illuminate the mechanisms underlying UV-mediated melanomagenesis

Abstract: The incidence of melanoma is one of the fastest growing of all tumor types in the United States and the number of cases worldwide has doubled in the past 30 years. Melanoma, which arises from melanocytes, is an extremely aggressive tumor that invades the vascular and lymphatic systems to establish tumors elsewhere in the body. Melanoma is a particularly resilient cancer and systemic therapy approaches have achieved minimal success against metastatic melanoma resulting in only a few FDA-approved treatments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…It is well documented that UV radiation and oxidative stress are linked [37], both of which can be differentially impacted by sex hormones. As redox biology is unique in melanocytes (evidenced by its regulation via melanocytic master regulator MiTF [38,39]), melanocytes may undergo a lineage-specific UV-induced DNA damage repair which is highly likely impacted by hormones and thus result in differential mutation rates.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that UV radiation and oxidative stress are linked [37], both of which can be differentially impacted by sex hormones. As redox biology is unique in melanocytes (evidenced by its regulation via melanocytic master regulator MiTF [38,39]), melanocytes may undergo a lineage-specific UV-induced DNA damage repair which is highly likely impacted by hormones and thus result in differential mutation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Despite all the knowledge about melanoma biology, this cancer remains one of the greatest challenges of our day [1,5,32,33], mainly due to the acquired resistance to chemotherapy and radiation [5,30]. Therefore, melanoma treatment remains essentially surgical [1,6,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…There are some established risk factors for melanoma development, like family history [9,10], genetic and hereditary factors, as well as environmental factors [1,2,3]. Nowadays, nutritional factors have emerged as possible modifiable risk factors for cutaneous melanoma, since a growing number of studies have shown that a balanced diet, rich in fruits and vegetables, is associated with lower risks for several types of cancer, including cutaneous melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Although the causal network of melanoma has not yet been fully elucidated [ 17 ], UV exposure is the most tangible environmental risk factor that can be readily modified by behavioral precautions [ 18 ]. Therefore, the purpose of this study was to explore the relationship between the hypothesized photobiological pathway and risk of melanoma.…”
Section: Introductionmentioning
confidence: 99%